Effects of long-term afforestation on soil water and carbon in the Alxa Plateau - Zhu, Xinglin; Si, Jianhua; He, Xiaohui; Jia, Bing; Zhou, Dongmeng; Wang, Chunlin; Qin, Jie; Liu, Zijin (Frontiers in Plant Science, 2024)
Plantations in dry and semi-arid areas significantly affect the soil's ability to store carbon and maintain a stable water balance. It is yet unclear, though, how planted trees in these regions might impact the soil's carbon and water levels. As a forest ages, it is unknown how soil water and soil carbon interact with one another. In order to conduct this study, four Saxaul plantations in the Alxa Plateau were chosen, with the neighboring mobile sandy (MS) ground serving as a control. The ages of the plantations ranged from 5 to 46 years. The major topics of the study included the relationship between soil water and soil carbon, changes in the 0-300 cm soil layer's soil water content (SWC), soil organic carbon (SOC), and soil inorganic carbon (SIC) following afforestation. The findings demonstrated that, in comparison to MS, afforestation considerably increased SOC and SIC stocks. In comparison to MS, the SIC grew by 4.02 kg m -2 , 4.12 kg m -2 , 5.12 kg m -2 , and 6.52 kg m -2 throughout periods of 5 years, 11 years, 22 years, and 46 years, respectively. SOC increased relative to MS by 2.55 kg m -2 , 2.91 kg m -2 , 3.53 kg m -2 , and 4.05 kg m -2 . Afforestation, however, also contributed to a considerable decline in deep SWC and an increase in the soil water deficit (SWD). In comparison to MS, the mean SWC values were lower at 5 years, 11 years, 22 years, and 46 years, respectively, by 0.48%, 1.37%, 1.56%, and 4.00%. The increase in soil carbon pool caused by sand afforestation actually came at the expense of a reduction in soil water due to a large negative association between deep SWC, SOC, and SIC. To limit SWC losses and encourage sustainable forest land development, we advocate suitable harvest management practices on forest land.